Pengaruh Tingkat Persepsi Masyarakat Kecamatan Dolok Silau terhadap Realisasi Rencana Pemekaran di Kabupaten Simalungun - Rohani Silalahi; Muhammad Husni Thamrin Nasution; Armansyah Matondang (Universitas Medan Area, 2019)
Blossoming district is a breakthrough to boost development in a region more quickly either through an increase in quality and quantity. This blossoming gives supervision so that the government can control the narrower region is becoming more focused. This is the underlying desire of the community to plan for expansion. Thus can be taken the formulation of the problem is whether there is influence of the level of public perception of the subdistrict dolok silau realizations against plans expansion in simalungun regency with the aim to know is there any influence the level of perception dolok sub society glare towards the realization of the plan of expansion in simalungun and to know how much influence the public perception of the subdistrict level Doloksilau againts the realization of the plan of expansion in simalungun. The form of this research is to use descriptive research with quantitative approach with a view to seeking influences between variables X (free) with the variable Y (tied). This research was conducted in the Doloksilau, simalungun Regency glare. While the collection of data is carried out by means of disseminating the questionnaire, interview and observation.